Expectations of justice in the age of Augustine - Uhalde, Kevin, 1971- (University of Pennsylvania Press, 2007)
Expectations of Justice in the Age of Augustine examines the complex and varying roles Christian bishops played during late antiquity and how their experiences fundamentally affected Christian ideals of divine justice.